Ethnobotanical knowledge and traditional uses of propolis among the Algerian population: a comparative and multivariate analysis - Brahimi, Hibat-allah; Oulebsir-Mohandkaci, Hakima; Hendel, Noui; Sarri, Madani (Ethnobotany Research and Applications, 2025)
Background: Propolis is a natural resinous substance collected by honeybees from tree buds and plant exudates, and is recognized for its beneficial biological properties. This study aims to provide a comparative overview of the various therapeutic, agri-food applications of propolis in Algeria, as well as the different forms and combinations with other natural products. Methods: This ethnobotanical study collected information on propolis use from 111 participants via semi-structured interviews. The data were analysed by calculating various parameters, including usage value and the relative frequency of citations. We used Multiple Component Analysis (MCA) and Principal Component Analysis (PCA) to determine all propolis properties. Cronbach's alpha analysis was used to assess the homogeneity of our survey. We used Pearson's test (α = 0.05) to test the relationship between propolis production parameters. Results: The ethnobotanical survey revealed that (73%) of participants possessed detailed knowledge of propolis' properties. The reported therapeutic benefits included support for the digestive system (40.5%), immune system (72%), along with wound treatment (66.7%). The study also found that, in Algeria, propolis is combined with other natural products (55.9%), to increase its effectiveness. With data reliability and homogeneity, analysis is shown to be stable and consistent across all questionnaire criteria. In addition, the Pearson test determined a correlation between the color of propolis in Algeria and the type of the plants. Conclusions: This study expands our understanding of propolis and its various uses, emphasizing its potential for development into pharmaceutical, dermatological and agricultural products. Keywords: Propolis, survey, Algeria, traditional uses, galenic forms, therapeutic properties, correlation analysis